2016
DOI: 10.1080/00103624.2016.1166380
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effects of Leucaena Biochar on Soil Acidity and Exchangeable Ions

Abstract: The amendment effect of Leucaena biochar was investigated in incubation study in acidic soil (pH (water (H 2 O)) = 4.5) of north-west India. The biochar (BC) was mixed at 2, 4 and 6 (%) with soil and change in soil pH, electrical conductivity (EC), ammonium (NH 4 ) and nitrate nitrogen (NO 3 -N), exchangeable bases calcium + magnesium, sodium) (Ca+Mg, K, Na), aluminum (Al) and Bray's phosphorus (P) were measured periodically. The mean increase in soil pH was 0.65, 1.35 and 2.0 unit at 2, 4 and 6% (w/w) of bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It is commonly reported that biochar benefits are related to an increase of CEC, sorption capacity, contribution of nutrients and creating a favourable environment for microbial growing (Blanco-Canqui, 2017). A decrease of aluminum toxicity induced by biochar application could increase soil pH and the concentrations of soil available nutrients, resulting in increased plant growth in several studies (Jha et al, 2016; Lin et al, 2018; Qian, Chen & Hu, 2013). In the current study, overall biochar application increased the concentrations of soil AP, AN and AK, thus benefiting plant nutrient uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly reported that biochar benefits are related to an increase of CEC, sorption capacity, contribution of nutrients and creating a favourable environment for microbial growing (Blanco-Canqui, 2017). A decrease of aluminum toxicity induced by biochar application could increase soil pH and the concentrations of soil available nutrients, resulting in increased plant growth in several studies (Jha et al, 2016; Lin et al, 2018; Qian, Chen & Hu, 2013). In the current study, overall biochar application increased the concentrations of soil AP, AN and AK, thus benefiting plant nutrient uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, biochar may act as both a source and sink of nutrients that are required for plant growth, and it can be strongly recommended for weathered poorly fertile soils for improving the nutrient retention and crop productivity. Apart from improving CEC, biochar could also improve the retention ability of Ca 2+ , Mg 2+ , K + and NH4 + ions in acidic soil (Alfisol) (Jha et al, 2016). However, most of the reports studying the effect of biochar on soil pH and CEC are laboratory based short-term experiments, with very few long-term field studies (Wang et al, 2021).…”
Section: Effect Of Biochar On Soil Ph and Cation Exchange Capacitymentioning
confidence: 99%
“…pH was found to increase gradually with increase in application rate of biochar [41]. The soil acidity ameliorating effect of Leucaena biochar was investigated in an incubation study in an acid soil (pH = 4.5) in northwest India by Jha et al [45] and it was reported that the mean increase in soil pH was 0.65, 1.35, and 2 units at 2 per cent, 4 per cent, and 6 per cent (w/w) of biochar incorporation respectively.…”
Section: Effect Of Biochar On Soil Phmentioning
confidence: 99%